PENEGAKAN HUKUM BAGI PELAKU TINDAK PIDANA PEMBUNUHAN DALAM PEMBELAAN TERPAKSA - Julaiddin, Julaiddin; Prayitno, Rangga (Program Magister Ilmu Hukum Universitas Ekasakti, 2020)
The value of justice is indeed abstract and can be a benchmark for the consideration of justice of each person is different. Depends on the value that bases its paradigm on justice itself. However, in practice there are still many violations and deviations from the purpose of the law itself, both intentional and unintentional. The role of law enforcement should be to carry out their duties in accordance with applicable provisions. The crime of murder in a forced defense, explaining an act of murder which is clear in the end has severe sanctions, both Indonesian criminal law. Therefore from the existence of compulsion or force impulse which is the reason for the eradication of criminal acts in bringing up a criminal act of murder, whether in the end was punished as a justification or forgiveness in Indonesian criminal law. Tindak pidana pembunuhan dalam pembelaan terpaksa, menjelaskan suatu tindak pidana pembunuhan yang sudah jelas pada akhirnya memiliki sanksi yang berat, baik itu hukum pidana Indonesia. Maka dari itu dengan adanya keterpaksaan atau dorongan daya paksa yang menjadi alasan penghapus tindak pidana dalam memunculkan suatu tindak pidana pembunuhan apakah pada akhirnya dihukumi menjadi suatu alasan pembenar ataukah pemaaf dalam hukum pidana Indonesia.